An alternative pathway for plant in vitro regeneration of chinaberry -tree Melia azedarach L. derived from the induction of somatic embryogenesis - Sharry, Sandra Elizabeth (2006)
A highly efficient somatic embryogenesis system and subsequent plant regeneration of chinaberry (Melia azedarach L.) was developed. Plants were regenerated from indirect somatic embryogenesis induction. Novel features of this improved protocol, include: a) Embryogenic callus induction with no addition of 2, 4-D in the culture media; b) Somatic embryos differentiation was achieved by using high concentration of cytokinins (BAP 10 mg/L) and adenine; c) 100% conversion of somatic embryos to plants was practically obtained and 100% of plants survived under greenhouse conditions; d) Addition of putrescine improved somatic embryos germination. The amount of somatic embryos produced by the pathway of indirect somatic embryogenesis was 447 per gram of fresh weight callus. Regenerated plants were phenotypically normal. The developed protocol established the potential to produce plantlets from cotyledon explants through somatic embryogenesis. It also presents itself as a highly efficient method for mass clonal propagation and conservation of Melia azedarach.